URGENSI PELATIHAN DAN PENGEMBANGAN SUMBER DAYA MANUSIA DALAM MENINGKATKAN KINERJA LEMBAGA PENDIDIKAN - Amalia, Rahma; Rahman, Danial (Program Studi Manajemen Pendidikan Islam, 2025)
Training and development of human resources (HR) play a strategic role in improving the performance of educational institutions amid policy changes and rapid technological advancement. The success of educational institutions is not solely determined by technological progress but is strongly influenced by the quality of educators and educational staff in managing learning processes and educational services. This study aims to examine the urgency of HR training and development as a strategy for enhancing institutional performance in education. The research employs a qualitative approach using a library research design by reviewing scholarly books, national and international journal articles, and relevant policy documents. Data were analyzed using descriptive qualitative analysis through thematic categorization, including concepts of HR training and development, their urgency in the digital era, and their implications for the performance of educational institutions. The findings indicate that training serves as a short-term, practical mechanism for improving operational competence, while HR development functions as a long-term strategic investment in preparing professional, adaptive, and competitive human resources. Systematically designed training and development programs through needs analysis, planning, implementation, and evaluation which contribute significantly to improving the quality of educational services and the effectiveness of institutional performance. Therefore, HR training and development should be positioned as an integral component of quality management in educational institutions to support sustainable performance improvement.